Psychological Capital Dengan Kinerja Karyawan Di Info Service Center - Ovinda, Scholastica Silvia Krisman (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Employee performance is very important for a company. Good performance will create quality human resources (HR) so that the company's goals and success can be realized. The existence of psychological capital can help individuals to explore their potential and help realize positive potential and self-confidence, therefore this research aims to test whether there is a relationship between psychological capital and employee performance at info service centers. This research uses quantitative correlational methods. The sampling method used was purposive sampling with a total sample of 56 employees at the information service center in the marketing work sector. This research uses data collection techniques in the form of employee performance data program results and the Psychological Capital Questionnaire (PCQ) instrumental scale proposed by Luthans, Youssef, and Avolio (2007). The data analysis technique used in this research is Spearman Rho. Based on the results of data analysis, a correlation coefficient was obtained. So the research results show that there is a very significant positive correlation between psychological capital and performance. Based on the categorization calculations for the two variables, it shows that the employee subjects in the info service center in the marketing sector have a high category, this shows that the hypothesis is accepted.